2012
DOI: 10.1007/s10120-012-0145-6
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for gastric neoplasm in patients with co-morbidities categorized according to the ASA Physical Status Classification

Abstract: Background Endoscopic submucosal dissection (ESD) has come to be widely performed for reduced invasiveness; however, its safety in patients with co-morbidities is not fully examined. We aimed to evaluate the safety and efficacy of gastric ESD with co-morbidities categorized according to ASA Physical Status Classification. Methods Two hundred and forty patients of ASA 1 (no co-morbidities), 268 of ASA 2 (mild), and 19 of ASA 3 (severe) were treated by ESD for gastric neoplasms. We retrospectively compared clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…A previous study [14] has reported that there was no significant difference in adverse events associated with ESD, such as delayed bleeding and perforation, among each ASA-PS group. In the present study, a slightly higher rate (10.6%) of adverse events associated with ESD in ASA-PS group 3 was observed; however, it was lower than what we previously reported [22] for patients with surgical gastrectomy (24.4%).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…A previous study [14] has reported that there was no significant difference in adverse events associated with ESD, such as delayed bleeding and perforation, among each ASA-PS group. In the present study, a slightly higher rate (10.6%) of adverse events associated with ESD in ASA-PS group 3 was observed; however, it was lower than what we previously reported [22] for patients with surgical gastrectomy (24.4%).…”
Section: Discussionmentioning
confidence: 80%
“…This study revealed that the long-term surgical outcome for patients with severe comorbidities, who were categorized as ASA-PS 3, was unfavorable. In a different study, no significant differences of adverse events associated with ESD, such as delayed bleeding and perforation, among ASA-PS 1, 2, and 3 patients, were observed [14]. The long-term outcome of ESD for ASA-PS 3 patients with EGC has not been determined.…”
Section: Introductionmentioning
confidence: 91%
“…14,17,22,28,30,34,42 However, 3 studies found significantly increased PPB rates in patients with chronic kidney disease 45 and undergoing dialysis. 18,46 Comorbidities 28, 45 and American Society of Anesthesiologists Physical Status Classification System status 47 were not identified to be associated with PPB, although 1 study found increased PPB risk in patients with significant comorbidities. 25 Other clinical factors were analyzed in a few studies.…”
Section: Risk Factors For Ppbmentioning
confidence: 90%
“…With respect to the safety evaluation of ESD in patients with comorbidities, Man-i et al [22] reported that comorbidity was a significant risk factor associated with complications unrelated to the ESD procedure (aspiration pneumonia, ischemic heart attack, arrhythmia and delirium). To the best of our knowledge, our study is the first to evaluate the relationship between diabetes mellitus and aspiration pneumonia after gastric ESD.…”
Section: Discussionmentioning
confidence: 99%